WAYS OF TRAINING STUDENTS BY PHYSICAL AND SPIRITUAL DEVELOPMENT USING FOLK GAMES - Abdullaev Oybek Qurbonovich (Scholar Express Journal, 2021)
The following article folk games as one of the most important factors in physical education and sport education, national samples of games recommended for use in classes and explain.
Keywords: Physical education and sports education; national games; medium; darkness